Moderating Influence of Conflict Resolution on the Relationship Between Transformational Leadership and Implementation of Constituency Development Fund Construction Projects in Public Secondary Schools in Kisumu County, Kenya - Wagude, Auma (European Scientific Journal, ESJ, 2019)
Transformational leadership is depicted mainly in four dimensions as idealized behavior, individual consideration, Intellectual stimulation, and inspirational motivation. The study sought to explore whether Conflict Resolutions moderates the relationship between Transformational leadership and implementation of Constituency Development Fund Construction Projects. The objective of the study was to establish the moderating influence of conflict resolution on the relationship between transformational leadership and implementation of CDF construction projects. Expost facto design was adopted in the study. Multifactor Leadership Questionnaire and Thomas Kilman Instruments, were used as tools for data collection. Quantitative data was analyzed descriptively using percentage, frequencies, mean, and standard deviation. Inferential analysis was carried out using correlations as well as regression analysis. The research hypothesis H0:1: The five predictors of transformational leadership and conflict resolution do not significantly explain the variance in implementation of CDF funded construction projects, was tested at Î± =0.05 using Pearson correlation coefficient and the finding indicated a P-value 0.00<0.05 which was statistically significant. It was therefore concluded that Conflict resolutions significantly influences the relationship between transformational leadership and implementation of CDF projects. It is therefore recommended that accredited MLQ coaching is desirable. From the regression analysis output, the study found F (2, 59) = 7.788 with p = 0.00 which imply that the regression model of conflict resolution and transformational leadership would best predict and implementation of CDF projects